2017
DOI: 10.1097/ij9.0000000000000007
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of internal hemipelvectomy for pelvic tumors: a developing country’s prospective

Abstract: Introduction:Previously, external hemipelvectomy was the mainstay of treatment for pelvic tumors. However, with technological advancements, limb salvage procedures such as internal hemipelvectomy have emerged as a viable alternative. However, there is limited literature available on long-term outcomes and complications of internal hemipelvectomy, especially from developing countries. Therefore, the objective of this study was to share our experience of internal hemipelvectomy at a tertiary care center in a dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…A study by Umer et al showed that the mean surgery time in pelvic resection was 356 min and the mean intraoperative blood loss was 1900 cc. Meanwhile, that study also showed that 62.5% of the tumor diameter was less than 10 cm [ 3 ]. Therefore, honed surgical and intraoperative bleeding control skills, which would result in less surgery time and blood loss, were substantial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Umer et al showed that the mean surgery time in pelvic resection was 356 min and the mean intraoperative blood loss was 1900 cc. Meanwhile, that study also showed that 62.5% of the tumor diameter was less than 10 cm [ 3 ]. Therefore, honed surgical and intraoperative bleeding control skills, which would result in less surgery time and blood loss, were substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al showed that the surgical margin was the factor most closely related to the local recurrence [ 29 ]. Several studies showed local recurrence rate 12,5–19% [ 3 , 30 , 31 ]. However, the patient may require further follow up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data management in the form of a formal tumor registry is also being practiced within our section of orthopedics. This has helped us put out numerous publications in the field of musculoskeletal oncology 32 47 . We feel that now this experience needs to be replicated on a national level and we are making efforts in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Among the issues faced in Pakistan, the most important factors influencing poor outcomes are late referrals, followed by inadequate diagnosis and treatment. [14] Perhaps, one of the most significant barriers in the advancement of therapy is the lack of cancer registries at national level which makes it difficult to gauge the burden of disease and short-/long-term outcomes. [15] The way forward is to utilize the hospital-based registries and provincial data to form minimum diagnostic and therapeutic guidelines, tailored to the needs of our own population.…”
mentioning
confidence: 99%